2021
DOI: 10.2991/absr.k.210609.040
|View full text |Cite
|
Sign up to set email alerts
|

Addition of Coconut Water and Banana Extract on MS Media to Stimulate PLB (Protocorm Like Bodies) Regeneration of Dendrobiumgatton sunray

Abstract: Organic material is widely used for propagation of orchids, namely coconut water, extracts of tomatoes, bananas, bean sprouts and potatoes which can be added to certain media as a provider of nutrients, amino acid minerals, and growth regulators. This study aims to determine the effect of the concentration of organic matter in coconut water and banana extract on MS media on the regeneration of PLB (protocorn like bodies) Dendrobiumgatton sunray. The study was conducted at the Biotechnology Laboratory, Faculty … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 3 publications
1
3
0
Order By: Relevance
“…A higher number of shoots was observed on the ½ MS medium supplemented with TDZ compared to that in other cytokinins (Corbellini et al, 2020). In another study, the highest rate of shoot proliferation was found in the MS medium containing banana puree and BA for Dendrobiumgatton sunray (Herawati, Ganefianti, & Romeida, 2021). These findings were similar to those of our study, which confirmed that modification of the nutrient medium using growth regulators and organic additives together stimulates shoot formation and growth induction.…”
Section: Plantlet Regenerationsupporting
confidence: 91%
“…A higher number of shoots was observed on the ½ MS medium supplemented with TDZ compared to that in other cytokinins (Corbellini et al, 2020). In another study, the highest rate of shoot proliferation was found in the MS medium containing banana puree and BA for Dendrobiumgatton sunray (Herawati, Ganefianti, & Romeida, 2021). These findings were similar to those of our study, which confirmed that modification of the nutrient medium using growth regulators and organic additives together stimulates shoot formation and growth induction.…”
Section: Plantlet Regenerationsupporting
confidence: 91%
“…Other studies reported that 150 g L -1 BE in a similar medium increased the root number of D. lasianthera (Utami et al, 2016). The combination of 2.5% BE and 10 -6 M BAP stimulated shoot emergence shortly with high number of shoots and leaves of Coelogyne pandurata (Nurfadilah et al, 2018), 75 g L -1 of BE induced 3.2 mm root length, 6.7 leaves per shoot and 2.3 roots per shoot in D. Gatton Sunray (Herawati et al, 2021), 100 ml L -1 of BE for Dendrobium sp. Suitable for PLBs multiplication and plantlet regeneration (Islam et al, 2016), 100 g L -1 BE increases the growth rate of D. lineale with 1.58 mg g -1 chlorophyll content (Mustika and Semiarti, 2021), 40 g L -1 BE and 20% coconut water (CW) induced high seed germination rate of Cattleya maxima up to 97.1% (Vilcherrez-Atoche et al, 2020), 50 g L -1 BE resulted in high regeneration frequency of C. pendulum (Kaur and Bhutani, 2012), and 20 gr L -1 BE was the best concentration for P. amabilis embryo regeneration (Nuryadin et al, 2020).…”
Section: Discussion Discussion Discussionmentioning
confidence: 97%
“…MS and KC media have been extensively used for efficient seed germination and in vitro propagation of several orchids [47][48][49][50]. VC medium, on the other hand, has been mainly utilized for the proliferation of protocorm-like bodies, which helped in the orchid clonal multiplication on a large scale [51]. Modification of culture media is made by variation in the concentration of nutrient components and integrating organic additives like coconut water (CW) and potato extract to suit the requirement of a particular species.…”
Section: Orchid Micropropagation Using Semi-solid Mediamentioning
confidence: 99%